Banana Ice Cream as An Eco-friendly Social Enterprise Product for Helping Cancer Patients During Treatment - Janne Hillary (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Banana ice cream is a fun food to eat and has both functions. The use of banana as main component of ice cream is expected to be a sustainable food, which is supporting Sustainable Development Goals (SDGs). The business of banana ice cream can be run for social purposes that make a profit, which will circle back for the needs of cancer patients. Design/methodology/approach: Break even point analysis used to determine economic feasibility of the business plan. Break even point would be reached when the total unit of selling banana ice cream as much as 3.024 scoops with sales value was 15.120.000 Indonesian Rupiah. The minimum time for recovering the initial investment was 151 days or 5 months. Banana ice cream business is feasible to be run. Findings: Cancer treatments often cause adverse effects at different levels. The adverse effect can greatly affect the patient's daily activities that may impair quality of life. New food products shall be developed to improve patient nutrition and reduce side effects from therapies. Originality/value: This paper is original Paper type: Research paper